Out-of-plane behaviour of masonry specimens strengthened with ECC under impact loading. (15th October 2018) - Pourfalah, Saeed; Cotsovos, Demetrios M.; Suryanto, Benny; Moatamedi, Mojtaba
Highlights: Investigate the behaviour of ECC-retrofitted masonry specimens subjected to impact loads. Confirmation of effectiveness of using the ECC layer(s) for retrofitting of masonry specimens subjected to impact loads. Comparing the performance of ECC-retrofitted masonry specimens under static and impact loads. Exhibiting the important aspects of specimens including the strain distribution through the ECC layer. Abstract: The work described herein sets out to investigate experimentally (via drop-weight testing) the out-of-plane behaviour of beam-like masonry specimens under impact loading when strengthened with a thin layer of engineered cementitious composite (ECC). The subject prismatic specimens essentially consist of a stack of ten bricks connected with mortar joints which are subjected to four-point bending tests. The impact load is applied via a steel mass allowed to fall from a certain height (drop-weight test). Specimens are subjected to consecutive impact tests until their collapse. Each specimen is strengthened by applying a thin ECC layer to the lower face of the prism (acting in tension) or to both, upper and lower, faces (acting in compression and tension respectively). These specimens are considered to provide a simplistic representation of a vertical strip of a masonry infill wall subjected to out-of-plane actions characterised by high loading rates and intensities (associated with impact and blast problems). The drop-weight tests reveal that the proposed strengthening method successfully increases the load-carrying capacity of the subject specimens compared to that observed under equivalent static testing, allowing them to absorb more effectively the energy introduced during impact without the production of debris. Nevertheless, it is important to mention that the behaviour exhibited by the ECC layer during impact testing is characterised by the formation of more localised and wider cracks compared to the fine distribution cracks observed when the same specimens are subjected to equivalent static testing.